Control of Alginate Core Size in Alginate-Poly (Lactic-Co-Glycolic) Acid Microparticles - Lio, Daniel (2016)
Core-shell alginate-poly (lactic-co-glycolic) acid (PLGA) microparticles are potential candidates to improve hydrophilic drug loading while facilitating controlled release. This report studies the influence of the alginate core size on the drug release profile of alginate-PLGA microparticles and its size. Microparticles are synthesized through double-emulsion fabrication via a concurrent ionotropic gelation and solvent extraction. The size of alginate core ranges from approximately 10, 50, to 100 μm when the emulsification method at the first step is homogenization, vortexing, or magnetic stirring, respectively. The second step emulsification for all three conditions is performed with magnetic stirring. Interestingly, although the alginate core has different sizes, alginate-PLGA microparticle diameter does not change. However, drug release profiles are dramatically different for microparticles comprising different-sized alginate cores. Specifically, taking calcein as a model drug, microparticles containing the smallest alginate core (10 μm) show the slowest release over a period of 26 days with burst release less than 1 %.